Effects of Arginine Vasopressin and V1 Receptor Antagonist on Cerebral Vasospasm Secondary to Subarachnoid Hemorrhage: An Experimental Study - Yilmaz, Dervis Mansuri; Haciyakupoglu, Ersin; Diril, Serkan; Sencar, Leman; Akgul, Erol; Polat, Sait; Haciyakupoglu, Sebahattin; Nazlican, Ersin (TURKISH NEUROSURGICAL SOC, 2018)
AIM: To examine morphological, radiological and biochemical effects of arginine vasopressin ( AV) and V1 receptor antagonist on cerebral vasospasm (CVS) after subarachnoid hemorrhage (SAH) in rabbits. MATERIAL and METHODS: Forty male New Zealand white rabbits were randomly divided into four groups comprising 10 rabbits each. The groups were

1) Control group, 2) SAH group, 3) SAH+AV group, 4) SAH+V1 antagonist group. Diameters of the basilar artery in all groups were measured on angiograms. All animals were sacrificed two days following basilar angiography and tissue samples of basilar artery were obtained under microscope immediate after craniectomy for ultrastructural and biochemical examinations. RESULTS: The artery diameters were found to be 50\% and 50\% at the 30th minute in the groups 2 and 3 respectively. In group 3, CVS was 13\% more in comparison with the 2nd group. In group 4, vascular constriction was 34.5\% at the 30th minute and about 30.9\% at the 300th minute. Despite the increase in regional blood flow, AV did not provide morphological change. Histological appearance was related to vascular stenosis due to CVS. Histological outcome was the best in group 4 because of less CVS. CONCLUSION: Arginine vasopressin plays an important role in CVS. We detected morphological and radiological recovery in basilar artery, besides moderate improvement due to AV receptor antagonist in CVS.
Keywords: Cerebral vasospasm; Subarachnoid hemorrhage; Arginine vasopressin; V1 receptor antagonist